Análisis Financiero al Microcomercial Jaramillo de la Ciudad de Loja, Periodo 2014-2015. Propuesta de Mejoramiento - Jaramillo Ramírez, Jheyns Antonia (2017)
The present thesis denominated "FINANCIAL ANALYSIS TO THE MICROCOMERCIAL JARAMILLO OF THE CITY OF SHOP, PERIOD 2014-2015. PROPOSAL FOR IMPROVEMENT." Was developed in compliance with one of the requirements established in the Regulation of Academic Regime prior to opting for the Degree and Degree of Engineering in Accounting and Auditing, Public Accountant-Auditor. As for its execution, the vertical analysis of the period 2014-2015 was carried out, which reflects the impact of the company's accounts, allowing the knowledge and determination of the composition of assets, liabilities and equity, as well as the elements of the income statement with the In order to establish the equitable distribution and according to the financial and operational needs of the Microcomercial; The horizontal analysis in which the growth or decrease in the accounts in the analyzed period was determined; The financial, liquidity, activity, debt, profitability, DuPont system and aggregate economic value (EVA) indicators were used to evaluate the financial, economic and operational performance of the company; Finally, the report and the improvement proposal were prepared for the benefit and development of the company